The effect of binary solution concentration and laser heating configuration on non-isothermal heat transfer and evaporation rate; Experimental Thermal and Fluid Science; Vol. 169 - Misyura S. Ya. Sergey Yakovlevich; Egorov R. I. Roman Igorevich; Zaitsev A. S. Aleksandr Sergeevich; Morozov V. S. Vladimir Sergeevich (2025, 2025)
Title screen